Air Quality Dynamics in the Vicinity of PT. Semen Padang, Padang City, Indonesia: Insights from Sentinel-5P Data During 2023 - Nanda, Fauzan Surya (Journal of the Physical Society of Indonesia, 2025)
This study aims to evaluate air quality in the vicinity of PT. Semen Padang, Padang City, West Sumatra, Indonesia, throughout 2023, utilizing data from the Copernicus Sentinel-5P satellite. The analysis reveals significant variations in the concentrations of pollutants such as carbon monoxide (CO), nitrogen dioxide (NO₂), sulfur dioxide (SO₂), and ozone (O₃). Higher pollutant concentrations were observed in urban areas, influenced by industrial activities and vehicular emissions. Levels of CO and O₃ frequently exceeded the World Health Organization (WHO) guidelines, posing potential health risks. Although most pollutant concentrations remained within safe limits, the findings underscore the importance of continuous air quality monitoring and the implementation of targeted mitigation measures to preserve environmental quality and safeguard public health, particularly in densely populated areas.